2017
DOI: 10.1016/j.jneuroim.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine activates caspase-1 in microglia via a novel pathway involving two inflammasomes

Abstract: Inflammasomes regulate microglial caspase-1 activation and subsequent neuroinflammatory processes in brain pathology. In the present study, we have identified inflammasomes causing caspase-1 activation following stimulation of microglia with lysophosphatidylcholine (LPC), a proinflammatory lipid generated under pathological conditions in the brain. LPC-induced caspase-1 activation in microglia was found to depend on LPS prestimulation, inflammasome NLRP3 and adaptor molecule ASC. Furthermore, knockdown of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Recently, Freeman et al showed that LPC-induced IL-1β secretion in BMDMs is dependent on NLRC4, NLRP3, caspase-1, and ASC, whereas the non-canonical inflammasome-associated protein caspase-11 is not involved. In addition, LPC could induce NLRC4 and NLRP3 inflammasome activation in microglia and astrocytes in a caspase-1 activation-dependent manner (61,62). LPC can induce IL-1β release in human monocytes (45).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Freeman et al showed that LPC-induced IL-1β secretion in BMDMs is dependent on NLRC4, NLRP3, caspase-1, and ASC, whereas the non-canonical inflammasome-associated protein caspase-11 is not involved. In addition, LPC could induce NLRC4 and NLRP3 inflammasome activation in microglia and astrocytes in a caspase-1 activation-dependent manner (61,62). LPC can induce IL-1β release in human monocytes (45).…”
Section: Discussionmentioning
confidence: 99%
“…Saturated FA, ceramide, cardiolipin and lyso-PC, have been reported to act as second signal activators of the NLRP3 inflammasome [ 17 , 18 , 51 , 52 , 68 ]. In this study, lyso-PC was found to activate both adipocyte and ATM NLRP3 inflammasomes in autocrine and paracrine manners.…”
Section: Discussionmentioning
confidence: 99%
“…LPC acts on a number of immune target cells, for example, it upregulates cytokine production and chemotaxis in macrophages and T-lymphocytes [32][33][34][35] . It also activates caspase-1 in microglia in the brain neuroinflammatory process 36 . PAF is also a potent activator of inflammatory cells involved in the innate immune system, including neutrophils, macrophages and platelets.…”
Section: Detection Of Mitochondrial Dysfunction In Ftd Using Serum LImentioning
confidence: 99%